Salt Hash Technique: an Innovation in Web Security (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Since the conception of World Wide Web by Sir Tim Berners-Lee, a lot  has been changed. The web has completely revolutionized our lives and  it continues to make a profound impact on the world. Today millions of  people use web services for communication, online shopping, online  banking etc; however web is crippled with its own security issues. Cyber  criminals have always posed a serious threat to millions of users who  rely heavily on web for their day to day activity and compelling the users  to live in complete oblivion of their compromised privacy. So in order to  protect the users who repose great trust in e-business from BAD GUYS of  cyber world, web security becomes imperative.One of the security aspects of web is Password Authentication and trans fer of data. Several kinds of attacks like Brute Force or Dictionary at tacks can severely breach the privacy of the online users by stealing users  credentials, so this paper highlights the innovation in Password Authenti cation using SALT HASHING to prevent time-memory trade-off attacks  and there by strengthening the web security.
Keywords: World Wide Web; Salt; hashing; salt password; Brute Force; web security